Polloneite, a new complex Pb(-Ag)-As-Sb sulfosalt from the Pollone mine, Apuan Alps, Tuscany, Italy. (1st December 2017) - Topa, Dan; Keutsch, Frank; Makovicky, Emil; Kolitsch, Uwe; Paar, Werner
Polloneite, ideally AgPb46As26Sb23S120, is a new N = 4 member of the sartorite homologous series. It occurs in a matrix of baryte from the Pizzone level of the Pollone baryte-pyrite-(Pb-Zn-Ag) deposit at Valdicastello Carducci, near Pietrasanta, in the Apuan Alps, Tuscany, Italy, as anhedral grains up to 0.5 mm across. The mineral is opaque, greyish black with a metallic lustre. In reflected light polloneite is white, bireflectance is moderate. Internal reflections are absent. Under crossed polars, anisotropism is moderate with rotation tints in brown-violet and deep grey. The reflectance data (%, air) are: 30.2, 42.4 at 470 nm, 28.8, 41.0 at 546 nm, 27.9, 39.8 at 589 nm and 26.0, 37.4 at 650 nm. Mohs hardness is 3–3½, microhardness VHN50 exhibits a mean value of 200 kg mm–2. The average results of 15 electron microprobe analyses of three grains are Ag 0.71(5), Pb 52.05(21), As 10.61(22), Sb 15.40(12), S 21.16(8), total 99.92(15) wt.%, corresponding to Ag1.20Pb45.76As25.79Sb23.04S120.21 (on the basis of Me + S = 216 apfu). The simplified formula AgPb46As26Sb23S120 is in accordance with the results of a crystal structure determination. The calculated density is 5.77 g cm–3. Polloneite is monoclinic, space group P21, a = 8.413(2), b = 25.901(5), c = 23.818(5) Å, β = 90.01(3)°, V = 5189.8(18) Å3, Z = 1. The strongest eight lines in the calculated powder-diffraction pattern [d in Å(I)hkl] are 3.795(100)(026), 3.414(60)(233), 3.238(69)(080), 3.020(97)(253), 2.922(82)(066), 2.738(73)(236), 2.375(79)(290) and 2.103(64)(400). Polloneite is a new N = 4 member of the sartorite homologous series with substantial Sb and small, but important, Ag content. It is a three-fold superstructure with a tripled unit-cell parameter, 7.9 Å, of sartorite homologues. In the As-Sb rich slabs, several types of crankshaft chains and isolated (As, Sb)–S polyhedra occur. A sequence of three different, tightly bonded double-layer fragments (broad ribbons) contains two asymmetric fragments with long crankshaft chains whereas the third fragment type, with Ag, contains small mirror-symmetrical metalloid groups and no crankshaft chains. This configuration can potentially cause order-disorder phenomena in the structure. The threefold superstructure and the mixed As-Sb character distinguish polloneite from veenite and from dufrénoysite, respectively.